2020
DOI: 10.3389/fphys.2020.00477
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Tussigenic Stimuli on Perceived Upper Airway Sensation and Motor Cough Response Following Total Laryngectomy

Abstract: Background: Total laryngectomy (TL) is standard intervention for carcinoma of the head and neck or, in cases of non-functional larynx, as a result of disease or radiation exposure. Laryngeal extirpation serves as a unique human model of both recurrent and superior laryngeal nerve section and offers insight into motor and sensory aspects of cough: both volitional and in response to tussigenic stimuli. While motor changes in cough function are expected among those status post-TL due to postoperative reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…This cohort of LT recipients who undergo denervation of the lower airway distal to anastomosis provides a unique contrast to published data in individuals undergoing total laryngectomy who lack laryngeal afferents. [49][50][51][52] The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung-volume related and pulmonary vagal afferent feedback was associated with modulation of cough. 22 Our RR findings are consistent with previous reports in patients with pulmonary disease, 53,54 and further align with a scoping systematic review which suggested that elevated RR is a physiologic risk factor for aspiration.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This cohort of LT recipients who undergo denervation of the lower airway distal to anastomosis provides a unique contrast to published data in individuals undergoing total laryngectomy who lack laryngeal afferents. [49][50][51][52] The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung-volume related and pulmonary vagal afferent feedback was associated with modulation of cough. 22 Our RR findings are consistent with previous reports in patients with pulmonary disease, 53,54 and further align with a scoping systematic review which suggested that elevated RR is a physiologic risk factor for aspiration.…”
Section: Discussionsupporting
confidence: 71%
“…No significant differences were observed in patient‐rated UTC across swallowing safety groups and at this point it does not appear another investigation on UTC in LT recipients is available for direct comparison. This cohort of LT recipients who undergo denervation of the lower airway distal to anastomosis provides a unique contrast to published data in individuals undergoing total laryngectomy who lack laryngeal afferents 49–52 . The observation that UTC appears diminished in both these populations may support findings in animal studies where, irrespective of if cough is stimulated at the larynx or intrathoracic airway, lung‐volume related and pulmonary vagal afferent feedback was associated with modulation of cough 22 …”
Section: Discussionmentioning
confidence: 67%
“…Fontana et al determined a reduction in PEFR and CVA in subjects with laryngectomy compared to age‐matched healthy subjects 27 . The decrease in PEFR with laryngectomy was further corroborated by Fullerton et al, 44 thus indicating a possible function of the larynx in catalyzing effective and maximal expiratory airflow during cough to achieve airway clearance.…”
Section: Discussionmentioning
confidence: 87%
“…Further, dysphagia-related hypotussia is associated with increased rates of pneumonia, reintubation, hospital readmission, and costs of care (31,(34)(35)(36)(37)(38). Complex deficits across the continuum of airway protection (i.e., swallow to cough) co-occur in multiple patient populations including: Parkinson's disease (39, 40), amyotrophic lateral sclerosis [ALS; (23,(41)(42)(43)], multiple sclerosis (44), atypical parkinsonism (31), progressive supranuclear palsy [PSP, (45)], cerebellar ataxia (25), stroke (41,46), head and neck cancer (47)(48)(49), cerebral palsy (50), spinal cord injury (51), lung transplantation (52), and cardiac surgery (37). Thus, to improve health and quality of life for this large and heterogeneous group of patients, it is critical that rehabilitation efforts include cough (4,15,31,38).…”
Section: Introductionmentioning
confidence: 99%